ICT application in achieving project success : a case study of a construction company in Malaysia - Yong Chan, Chua (2014)
ICT has been shown to be a very important tool in assisting the construction industry to deal with the increasing complexity of projects as well as the increasing demands of clients and regulators. In most developed countries that had raised their fund for ICT investment, it resulted that the productivity has increased within their construction industry. However, Malaysia is slowly adopting ICT in construction industry compare to the other countries. Therefore, this research is to study how the ICT assist in the construction industry and whether it can help in achieving project success. It’s also evaluate the factors of ICT applications to see what are the factors that influence ICT implementation. A construction company in Malaysia was chosen to be a case for study. There are totally eight interviewees selected from the high level management of the construction company. The research shows that the factors affecting the ICT implementation include individual, organizational, and technological level factors. Besides that, the result shows that the types of the ICT adopted by the company are covering the electronic communication system, documentation and accounting, quantity surveying, architectural/engineering design and drawing, and also project planning and tracking. The results also show that the ICT can assist in achieving construction project success by meeting the criteria, which are time, cost, quality, scope and customer satisfaction. As a conclusion, ICT is one of the key determinants of the project success. The possibility of the project success will increase if the ICT implementation practices are effective in the construction industry. This study can provide the baseline information for those who want to apply ICT in the construction industry